Determinação da vazão máxima da bacia hidrográfica do Rio do Campo utilizando o software HEC-HMS - Rodrigues Junior, Rosinaldo de Souza (2019)
Population growth and territorial expansion contribute to the increase of the impermeable area and consequently changes the maximum flow of nearby water bodies. The maximum flow is used in the design of hydraulic works, such as bridges, pipelines, dams, among others, and can be obtained through direct and indirect methods, among them is the hydrological modeling. Thus, the objective of this study was to determine the hydrological characteristics of the Rio do Campo watershed, as well as to determine the maximum flow from the SCS Curve Number loss method and the methods of transformation of the Snyder unit hydrogram and the SCS hydrogram, for the return times of 25, 50 and 100 years using the HEC-HMS software. For this determination, the Rio do Campo basin was divided into four sub-basins, and information was obtained on land use and occupation, characteristics of the main river (slope and length), area of the basin and soil present. The results obtained for the flow in the exuturium were 296,2 m³.s-1 , 368,5 m³.s-1 and 453,6 m³.s-1 using the SCS method and 234,6 m³.s-1 , 291 m³.s-1 and 357,8 m³.s-1 for the Snyder method, in concentration times of 25, 50 and 100 years, respectively. The flow of the exutrium for a return time of 25 years, obtained a difference of 11,61 % between the SCS method and the Snyder method, while for the return times of 50 and 100 years this difference corresponded to 11,75 % and 11,81 %, respectively. The maximum specific flow was 0,7734 m3 .s-1 .Km-2 ; 0,9622 m3 .s-1 .Km-2 and 1,1844 m3 .s-1 .Km-2 for the SCS method and equal to 0.6126 m3 .s-1 .Km-2 , 0,7599 m3 .s-1 .Km-2 and 0,9343 m3 .s-1 .Km-2 for the Snyder method, considering the return times of 25, 50 and 100 years. Thus, it is concluded that the study is of great importance for the survey of the hydrological characteristics of the Rio do Campo basin, such as drainage area, slope, use and occupation, as well as for the determination of the maximum flow rate that allows a management of risks related to floods and hydraulic works.